Long-wave infrared pulsed external-cavity QCL spectrometer using a hollow waveguide gas cell - Francis, Daniel; Hodgkinson, Jane; Tatam, Ralph P. (Optica Publishing Group, 2024)
A spectrometer built using an external cavity pulsed quantum cascade laser is described. The spectrometer has a tuning range from 10 – 13 µm (1,000 – 769 cm−1) and is designed to target volatile organic compounds (VOCs) which often exhibit water-free molecular absorption within the region. The spectrometer utilizes a hollow silica waveguide gas cell which has an internal volume of a few millilitres, a fast response time (∼1 s), and is advantageous when only low sample volumes, similar to the cell volume, are available. Propane is used as a test gas because it is easy to handle, and its spectral profile is comparable to VOCs of interest. Its absorption in the region is primarily within the ν21 band which spans from 10.55 – 11.16 µm (948 – 896 cm−1). Spectral measurements at a range of concentrations show good linearity and an Allan deviation of absorbance values recorded over a 100-minute period indicates a minimum detectable absorbance of 3.5×10−5 at an integration time of 75 s.